Variation of fruit morphology and genetic divergence of indigenous pointed gourd - Islam, Siddikul; Datta, Suchand; Das, Bimal; Basfore, Shibnath; Chatterjee, Ranjit; Sarkar, Ram Krishna (Bangladesh Journal of Botany, 2024)
Thirty one indigenous pointed gourd genotypes were studied in Terai region of West Bengal, India to observe variation of fruit morphology and genetic divergence using Mahalanobis D2 statistics and principal component analysis. The field experiment was designed in RBD with three replications at Uttar Banga Krishi Viswavidyalaya, West Bengal, India during the year 2018-19 and 2019-20. All the genotypes were arranged into eight divergent clusters in which cluster I included maximum number followed by cluster II. The highest contribution towards genetic diversity was shown for node at the first female flower (37.85%) followed by chlorophyll a content of leaf (16.77%) and seeds per fruit (12.04%). Principal component-1 had maximum variability (43.83%) with positive loading for the characters like node at the first female flower (0.298), appearance of first female flower (0.265), days to fruit maturity (0.194) and internodal length (0.137). Based on the inter and intra cluster distance cross combinations in between lines PCP-17 and PCP-19, PCP-17 and PCP-9, PCP-17 and PCP-28, PCP-19 and PCP-11, PCP-14 and PCP-9 and PCP-23 and PCP-10 may be utilized in future improvement programme of pointed gourd. Bangladesh J. Bot. 53(1): 193-201, 2024 (March)